Enhanced Optimization Strategy to Maximize Achievable Rate of Millimeter-Wave Full-Duplex UAV on Multiple User - Harinitha, Dwi; Zakia, Irma; Iskandar (Emerging Science Journal, 2025)
This study proposes an enhanced optimization strategy to maximize the achievable data rate of millimeter-wave (mmWave) full-duplex (FD) unmanned aerial vehicles (UAVs) in multi-user scenarios. The objective is to address signal degradation from high-frequency path loss and self-interference while ensuring efficient resource allocation across multiple user equipment (UEs). A joint optimization framework is introduced, integrating UAV positioning, beamforming vector design at both the gateway and UAV, and power allocation. Initially, the Alternating Interference Suppression (AIS) algorithm is adapted for multiple UEs, but due to emerging non-convexity, the problem is reformulated using a first-order approximation approach. The solution is decomposed into two iterative sub-problems—optimizing UAV location and then solving for beamforming and power distribution. MATLAB-based simulations validate the proposed approach, revealing a threefold increase in achievable data rate and a 40.85% improvement in power efficiency compared to non-optimized systems. The novelty of this work lies in its scalable multi-user adaptation and its integrated, power-aware optimization algorithm, outperforming conventional FD and half-duplex strategies. This contribution significantly advances the design of efficient, high-throughput UAV communication systems for next-generation wireless networks, especially in environments with frequent line-of-sight obstructions.